PENGARUH EDUKASI MEDIA DENGUE CARDS GAME TERHADAP PENGETAHUAN PENCEGAHAN DBD DI SDN CIPTOMULYO 2 KOTA MALANG - mufida, aisyah rohma; Jupriyono, Jupriyono; Winarni, Sri (Jurnal Pendidikan Kesehatan (e-Journal), 2024)
There were 569 dengue fever cases in Malang City in 2022, of which 225 dengue fever sufferers were dominated by children aged 1-14 years. The additional cases are due to lack of exposure to health information which causes children to have low awareness of prevention efforts. Efforts that can be made are by providing health promotion education using dengue card game media which is presented in the form of pictures and descriptions so that it has a special attraction for children to learn about it. This research uses a pre-experimental design with a one group pre-test post-test design approach. The population is all students at SDN Ciptomulyo 2 Malang City, totaling 199. The sample in this study used a purposive sampling technique with a sample size of 50 respondents. The instrument used was a questionnaire. The results of this research show that the level of students' knowledge before being given education about dengue fever with a percentage of good knowledge level of 4% after being given education experienced a significant increase to 90%. Based on the results of the Wilcoxon test with a significance level of 0.05, a p value of 0.000 was obtained, thus this research rejects Ho, meaning that there is a significant influence between education using dengue cards game media on changes in elementary school students' knowledge. This Dengue Cards Game media can be used as an alternative in providing education on dengue prevention.